A review on food processing and preparation methods for altering fish allergenicity. Issue 7 (12th April 2022) - Dasanayaka, Binaka Prabashini; Li, Zhenxing; Pramod, Siddanakoppalu Narayana; Chen, Yan; Khan, Mati Ullah; Lin, Hong
Abstract: People eat many varieties of food to satiate their hunger. Among them, a few numbers of food cause overreaction of the body's immune system, and fish holds a permanent position on that list. Processing methods, including one treatment or a combination, can have different effects on the allergenic potential of food proteins. An important point to note, however, is that not all of these methods can eliminate the potential for protein allergy. Thus, it is essential to understand the risk involved with the consumption of processed fish and its derivatives. Fish could be prepared in various ways before come to the dining plate. It has shown some of these methods can effectively manipulate the allergenicity owing to the alterations occurred in the protein conformation. This article provides an overview of the impact of fish processing methods (thermal and non-thermal) on the allergenic potential of fish along with possible causative structural modification provokes allergen stability. The article begins with current trends related to fish consumption, proceeds with the prevalence and underlying mechanism of fish allergy. Properties of clinically relevant fish proteins, projected IgE epitopes of PV, cross-reactivity of fish allergens are also addressed in this context to understand and compare the behavioral patterns of PV profiles of different species on processing methods.